Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids, with Cranial and Caudal Extension - Mahmood Mubasher; Aseel Sukik; Ahmed Hassan El Beltagi; Ali Rahil (Case Reports in Neurological Medicine)
A 23-year-old lady presented with vertigo and imbalance in walking, blurring of vision, diplopia, and headache, in addition to numbness in the lower limbs over a period of six days. On examination patient had nystagmus, ataxia, positive Romberg test, and hyperreflexia. MRI examination of the brain and spinal cord showed evidence of faint bright signal intensity foci in T2/FLAIR involving bilateral cerebral hemispheres, subcortical deep white matter, bilateral thalami, posterior pons and left brachium pontis, and basal ganglia, with small nodular enhancement that aligned along curvilinear structures; those lesions also were apparent along the spinal cord at multiple levels. The clinical and radiological features suggested CLIPPERS (chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids) syndrome. Symptoms improved dramatically with high dose oral corticosteroids. Our report addresses the radiological and clinical pattern of a case of CLIPPERS rhombencephalitis, with added superior and inferior extension to involve the brain and spinal cord, which is to emphasize the importance of raising the awareness of this disease and the combined role of radiologist and physicians for the diagnosis of this potentially treatable entity, responsive to glucocorticosteroid immunosuppression.